1999
DOI: 10.1046/j.1460-9568.1999.00536.x
|View full text |Cite
|
Sign up to set email alerts
|

Auditory activation of cortical visual areas in cats after early visual deprivation

Abstract: Auditory activation of the primary visual cortex (area 17) and two extrastriate visual cortical areas - the anterolateral lateral suprasylvian area (ALLS) and anteromedial lateral suprasylvian area (AMLS), was investigated in visually impaired cats. Impairment was accomplished shortly after birth by bilateral eyelid suturing (binocularly deprived cats, BD) or bilateral enucleation (binocularly enucleated cats, BE). In BE cats, the optic nerve and chiasm were entirely degenerated. No cortical atrophy or cytoarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 46 publications
(68 reference statements)
3
37
0
Order By: Relevance
“…In their classic study, Rauschecker and Korte (2) showed that the ectosylvian visual area responded vigorously to auditory and/or somatosensory stimuli in cats visually deprived from birth. Similar developmental studies have been performed in a variety of species and their common finding was that cortical areas normally devoted to processing one sensory modality were converted to the other sensory systems following early visual deprivation (3)(4)(5)(6)(7)(8) or early deafening (9-13, but see 14).…”
mentioning
confidence: 70%
“…In their classic study, Rauschecker and Korte (2) showed that the ectosylvian visual area responded vigorously to auditory and/or somatosensory stimuli in cats visually deprived from birth. Similar developmental studies have been performed in a variety of species and their common finding was that cortical areas normally devoted to processing one sensory modality were converted to the other sensory systems following early visual deprivation (3)(4)(5)(6)(7)(8) or early deafening (9-13, but see 14).…”
mentioning
confidence: 70%
“…This phenomenon is particularly prominent in sensory deprivation. The visual cortex becomes recruited for tactile and auditory perception in the blind (1,2,6,8,13,16,17,(41)(42)(43), and the auditory cortex becomes recruited for tactile and visual perception in the deaf (20-23, 26-29, 44). Such large-scale reorganization is also possible after intensive training in nondeprived subjects (5,12,(45)(46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, experiments in kittens have demonstrated that projections from the auditory cortex to the occipital cortex are eliminated either through cell death or retraction of exuberant collaterals during the synaptic pruning phase (Dehay et al, 1988;Innocenti et al, 1988). Importantly, in kittens deprived of vision at birth, these extrinsic connections to the occipital cortex seem to remain (Berman, 1991;Yaka et al, 1999). It is thus plausible that in the absence of competitive visual inputs during the synaptic stabilization phase, a significant number of direct auditory connections to the occipital cortex persist.…”
Section: Discussionmentioning
confidence: 99%